A Realistic Model for Catastrophic External Haemorrhage Training. Issue 2 (1st June 2007) - Moorhouse, I; Thurgood, A; Thurgood, A; Walker, N; Cooper, B; Mahoney, PF; Hodgetts, TJ
Abstract : External haemorrhage is a significant cause of combat morbidity and mortality. UK DMS have introduced topical haemostatic agents (HemCon®, QuikClot®) for use as an adjunct to control catastrophic external haemorrhage. Realistic training in new equipment is essential. A model is described that is simple, reproducible, valid, realistic and currently unique in its opportunity to train soldiers to deal with life-threatening external bleeding, without recourse to live animal training. The model has been used successfully to train UK DMS medics, nurses and doctors in Afghanistan.